Assessment of the effectiveness of scenarios for the adaptation of the regional economy to external economic constraints - A. V. Rezepin; I. V. Danilova; N. V. Pravdina (Модернизация, инновация, развитие)
Purpose: is to evaluate the effectiveness of adaptation scenarios to the external economic constraints of the regional economy, taking into account changes in the structural characteristics of the industrial sector.Methods: to determine the "sufficient" and "necessary" conditions for effective adaptation of regions to foreign economic constraints, the study used qualitative comparative analysis using fuzzy sets (fsQCA) and the Quine-McCluskey algorithm. 27 combinations of qualitative characteristics of regional adaptation have been identified, taking into account changes in the sectoral structure of production, the degree of openness of the economy, the level of manufacturability and innovation of products. Simplification of logical expressions made it possible to identify 6 scenarios and evaluate their effectiveness as the dynamism of industrial production growth.Results: the generalization of scientific publications on the research topic and the analysis of the practice of adapting regions to foreign economic constraints in 2008, 2014-2015 made it possible to identify three basic scenarios: "conservation", "reconstruction" and "restructuring" of the industrial profile of the region. Equifinality has been established when adaptation results similar in terms of industrial production dynamics are observed in regions with different combinations of structural changes in the industrial profile. Refined adaptation scenarios have been identified that contribute to the dynamization of recovery growth and subsequent economic development of the regions.Conclusions and Relevance: it has been established that foreign economic constraints produce structural changes in the industrial profile of the regions. The response of regions to external shocks is specific in terms of the scale and directions of structural changes. Effective adaptation scenarios have been identified, and recommendations have been formulated to improve the structural and industrial policies of the regions for the period of restrictions in 2022.